Beyond dualism: The sacred value of biological totems in Christian Platonic thought - Zhilong Yan; Aixin Zhang (HTS Teologiese Studies/Theological Studies)
The Christian Platonic theology and philosophy have been criticised for many years by various scholars. The dualistic perspective may belittle the value of plant and animal kingdoms, entangling humans in anthropocentric bias and promoting hierarchical systems. However, subsequent theologians and philosophers interpreted these works in ways that allowed negative perspectives and misunderstandings of the material world and its symbols to develop, leaving a mark on history. Therefore, the discussed Christian Platonic theology represents a specific spiritual gnostic view with a unique perspective on spirituality. It values all living beings as uniquely revealing their divine nature. Therefore, although hierarchical views may exist, it does not mean any being should dominate. Instead, it means that, in the being’s participation in God’s manifestation, the being adds something unique regarding some of God’s features. This perspective allows for revising religious viewpoints that have been misunderstood or overly simplified and promotes a fundamental humanistic spirit of care for all living beings’ inborn spiritual significance.